Real leaders negotiate! : gaining, using, and keeping the power to lead through negotiation - Salacuse, Jeswald W. (Palgrave Macmillan, 2017)
This book examines the central role of negotiation in gaining, exercising, and retaining leadership within organizations, large and small, public and private. Its aim is to instruct readers on the way to use negotiation to lead effectively. For far too long conventional wisdom has proposed that strong leaders refuse to negotiate, viewing negotiation as a sign of weakness. Leading people requires charisma, vision, and a commanding presence, not the tricks for making deals. For many executives, negotiation is a tool to use outside the organization to deal with customers, suppliers, and creditors. Inside the organization, it's strictly "my way or the highway." Salacuse explains that leaders can increase their effectiveness by using negotiation in each of the three phases of the leadership lifecycle: 1) leadership attainment, 2) leadership action; and 3) leadership preservation and loss. Drawing on experience in wide variety of settings, including the author's own leadership positions, the book will examine high profile leadership cases such as the rise and fall of Carly Fiorina at Hewlett-Packard, the skillful negotiations by Warren Buffet to save Salomon Brothers from extinction, and the successful efforts by the partners at Goldman Sachs to negotiate a new vision and direction for that financial giant. Leaders and managers should pick up this book to learn how effective negotiation is essential to both gaining and exercising leadership and to overcoming threats to a leader's position.
Keywords: Negotiation.; Leadership.; elektronické knihy; electronic books